Constrained mate choice in social monogamy and the stress of having an unattractive partner - Griffith, Simon C. (The Royal Society, 2011)
In socially monogamous animals, mate choice is constrained by the availability of unpaired individuals in the local population. Here, we experimentally investigate the physiological stress endured by a female (the choosy sex) when pairing with a non-preferred social partner. In two experimental contexts, female Gouldian finches (Erythrura gouldiae) socially paired with poor-quality mates had levels of circulating corticosterone that were three to four times higher than those observed in females that were paired with preferred mates. The elevated level of this stress hormone in response to partner quality was observed within 12 h of the experimental introduction and maintained over a period of several weeks. Our findings demonstrate the extent of intra-individual conflict that occurs when individuals are forced to make mate-choice decisions that are not perfectly aligned with mate-choice preferences. The elevated level of corticosterone also suggests a mechanistic route through which females might adaptively manage their responses to intersexual conflict over reproductive investment.